Preparation method for synthesizing NaxCoO2 nano thermoelectric material by combining self-propagating method and cold pressing method and application of NaxCoO2 nano thermoelectric material

By combining self-propagation method and cold pressing method to synthesize NaxCoO2 nanothermoelectric materials, the problems of complex preparation methods and small output in the prior art are solved, and high efficiency, low cost, high crystallinity and high thermoelectric properties are achieved, suitable for the preparation of materials with high efficiency and low cost. High temperature zone application.

CN119118211APending Publication Date: 2024-12-13YANGTZE DELTA REGION INST (QUZHOU) UNIV OF ELECTRONIC SCI & TECH OF CHINA
View PDF 0 Cites 1 Cited by

Patent Information

Application Number
CN202411252328.2
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-09-06
Publication Date
2024-12-13

AI Technical Summary

Technical Problem

The existing preparation methods of NaxCoO2 thermoelectric materials have problems such as small production output, complex process, low orientation, poor crystallinity and high cost, which limit the promotion and industrial production of thermal energy collection applications in high-temperature zones.

Method used

NaxCoO2 nanothermoelectric materials were synthesized by combining self-propagation method and cold pressing method. The precursor powder was obtained by dissolving sodium nitrate and cobalt nitrate hexahydrate in citric acid solution and heating and burning, and then calcining by muffle furnace and pressure treatment of tablet press to form Disc-type polycrystalline blocks and annealed at high temperature to improve density.

Benefits of technology

It realizes high crystallinity and high thermoelectric properties of NaxCoO2 thermoelectric materials with simple process, fast preparation, large output and low cost. It is suitable for high-temperature temperature difference power generation devices, temperature sensors and refrigeration sheets and other fields, improving the thermoelectric conversion performance of the material.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119118211A_ABST
    Figure CN119118211A_ABST
Patent Text Reader

Abstract

The invention relates to the technical field of nano materials, and provides a preparation method and application of a NaxCoO2 nano thermoelectric material synthesized by combining a self-propagating method and a cold pressing method. The invention aims to solve the problems of low production yield, complex process, low orientation degree, poor crystallinity and high cost of the conventional NaxCoO2 preparation method and improve the application of the NaxCoO2 in heat energy collection in a high-temperature area. According to the main scheme, the preparation method comprises the following steps: dissolving sodium nitrate and cobalt nitrate hexahydrate in a citric acid solution in proportion, heating to self-propagating combustion to obtain precursor powder, calcining, tabletting to obtain a NaxCoO2 polycrystalline block, and annealing to improve the compactness; the preparation method is used in the fields of thermoelectric power generation in a high-temperature area, refrigeration, medical treatment, sensing and the like, has the advantages of simple process, high preparation speed, high yield, low cost, good crystallinity and high thermoelectric performance, realizes quick preparation of the high-temperature thermoelectric material with high thermoelectric performance and high crystallinity, and has relatively high commercial and practical values.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention belongs to the technical field of nanomaterials, and particularly relates to a method for synthesizing Na by combining a self-propagating method and a cold pressing method. x CoO2 nano-thermoelectric materials, preparation methods and applications. Background Art

[0002] Cobalt oxides have become one of the focuses of current research on high-temperature thermoelectric materials due to their unique layered structure and thermoelectric properties. x CoO2 is an alkaline ternary oxide group with rich magnetic properties and structural phase diagram. Its structural form is a bronze ore-type layered structure composed of insulating Na+ layers and conductive CoO2 layers stacked along the c-axis. It has attracted extensive research attention because of its high thermoelectric figure of merit at high temperatures. It is widely used in aerospace, temperature difference power generation, refrigeration, medical treatment, and sensing. The thermoelectric performance of thermoelectric materials is often expressed by the dimensionless constant ZT. The specific formula is: ZT = (S 2 ρ) / κT, where S is the Seebeck coefficient, ρ is the resistivity, κ is the thermal conductivity, and T is the absolute temperature. Currently, many preparation methods are used to develop Na2O3 with high thermoelectric performance. x CoO2, such as solid phase reaction method and spark plasma sintering, these methods are usually limited by production conditions, have the problems of low production output, complex process, low orientation, poor crystallinity and high cost, which limits the Na x CoO2 has been widely used in the field of thermoelectric conversion technology in high temperature areas. Therefore, Na x CoO2 thermoelectric materials have important practical significance.

[0003] Through the above analysis, the problems and defects of the existing technology are: x The preparation method of CoO2 has the disadvantages of low production output, complex process, low orientation, poor crystallinity and high cost, which limits the development of Na x Application of CoO2 thermoelectric materials in thermal energy collection in high temperature areas. Summary of the invention

[0004] In view of the problems existing in the prior art, the present invention provides a method for synthesizing Na by combining self-propagating and cold pressing method. x CoO2 nano-thermoelectric materials, preparation methods and applications.

[0005] The present invention is achieved by combining a self-propagating method and a cold pressing method to synthesize Na x The method for preparing CoO2 nano thermoelectric material comprises the following steps:

[0006] Step 1, dissolve sodium nitrate and cobalt nitrate hexahydrate in 100 ml of 72 g / L citric acid solution at a ratio of 1.1:2.

[0007] Step 2: Heat the mixed solution on a hot plate at 300° C. until the solution becomes a viscous reddish-brown liquid. Continue heating, and the viscous liquid will burn in a self-propagating manner to eventually obtain a black precursor powder.

[0008] Step 3: The obtained black precursor powder is placed in a muffle furnace and calcined for 2 h in an air atmosphere at 800 °C to remove organic matter. A tablet press is then used to apply a certain pressure to the obtained powder to obtain a disc-shaped Na x CoO2 polycrystalline block, the polycrystalline block is annealed again at 800℃ to improve its density.

[0009] Furthermore, the beaker in step 1 is placed on a constant temperature heating magnetic stirrer and stirred at a speed of 500 r / min for 10 min.

[0010] Furthermore, the reaction process in step 2 is completed in a fume hood.

[0011] Further, the Na obtained in step 3 x The pressure applied by CoO2 is 40MPa.

[0012] The present invention also provides a method for synthesizing Na by combining a self-propagating method and a cold pressing method. x CoO2 nano thermoelectric material, the Na x The CoO2 nano thermoelectric material is prepared by using the above method.

[0013] The present invention also provides a temperature difference power generation device suitable for high temperature areas, wherein the temperature difference power generation device utilizes the above-mentioned Na x CoO2 nano thermoelectric material is prepared.

[0014] The present invention also provides a temperature sensor, wherein the temperature sensor utilizes the above-mentioned Na x CoO2 nano thermoelectric material is prepared.

[0015] The present invention also provides a semiconductor refrigeration piece, wherein the refrigeration device utilizes the above-mentioned Na x C o O2 nano thermoelectric material is prepared.

[0016] In combination with the above technical solutions and the technical problems solved, the advantages and positive effects of the technical solutions to be protected by the present invention are as follows:

[0017] 1. The technical solution to be protected by the present invention has a simple process, fast preparation, large single preparation amount, and is easy to scale up industrially; the reagents used in the solution of the present invention are low in cost and easy to obtain; and the prepared Na x CoO2 has good crystallinity and high thermoelectric performance, and the material purity is high, so it can be easily processed into thermoelectric devices later.

[0018] 2. The technical solution to be protected by the present invention has the technical characteristics of rapid preparation, large output and low cost; the present invention prepares a method for synthesizing Na by combining the self-propagating method and the cold pressing method. x CoO2 thermoelectric material has the characteristics of good crystallinity and high thermoelectric performance.

[0019] 3. The expected benefits and commercial value of the technical solution of the present invention after transformation are as follows: The present invention realizes the high-temperature thermoelectric material Na with high thermoelectric performance and high crystallinity. x CoO2 can be prepared quickly, and the resulting thermoelectric material has uniform size, simple process, large synthesis yield, and is easy to scale up industrially, with high commercial and practical value.

[0020] 4. Synthesis of Na by self-propagation method x CoO2 nano-thermoelectric material is a common preparation method for cobalt salts. Usually, the product obtained by self-propagation is subjected to high-temperature heat treatment and then SPS sintering. This method has two defects: first, the SPS sintering method is difficult to synthesize in large quantities, and usually only a round piece sample with a diameter of 20mm and a thickness of 2mm can be synthesized; second, the obtained sample lacks scattering centers, which leads to a high overall thermal conductivity of the material. By cold pressing the material before high-temperature heat treatment, and then selecting a muffle furnace of appropriate size for sintering, the area of ​​material sintering processing can be greatly increased, and industrial mass production of materials can be realized; in addition, Figure 2 As can be seen, in addition to the flake Na x In addition to CoO2 polycrystalline thermoelectric materials, there are also smaller nanoparticles. These small nanoparticles increase the scattering of phonons on the crystal surface of the material. According to the lattice thermal conductivity formula: Where C V , v, and l are the constant volume heat capacity, the average rate of phonon diffusion, and the mean free path, respectively. Due to the scattering of phonons by grain boundaries, the average rate and the mean free path both decrease, resulting in a decrease in lattice thermal conductivity. At the same time, for electronic thermal conductivity: K e =Lneμ, where L, n, e, and μ are the Lorentz constant, carrier concentration, electron charge, and electron mobility, respectively. Grain boundary scattering reduces the electron mobility μ, which reduces the electronic thermal conductivity. In summary, due to the total thermal conductivity: κ = K L +K e Therefore, grain boundary scattering reduces the total thermal conductivity. According to the material ZT value formula ZT=(S2 ρ) / κT, the decrease in thermal conductivity κ increases ZT, thereby improving the thermoelectric conversion performance of thermoelectric materials. Figure 7 , Figure 8 It can be found that the thermal conductivity of the thermoelectric material obtained by cold pressing is about 3 times lower. BRIEF DESCRIPTION OF THE DRAWINGS

[0021] Figure 1 The present invention provides a method for synthesizing Na by combining a self-propagating method and a cold pressing method. x Flow chart of the preparation method of CoO2;

[0022] Figure 2 is a scanning electron microscope image of the product obtained in Example 1 of the present invention;

[0023] Figure 3 is the X-ray diffraction pattern of the product obtained in Example 1 of the present invention;

[0024] Figure 4 is a Seebeck coefficient diagram of the product obtained in Example 1 of the present invention;

[0025] Figure 5 is the conductivity diagram of the product obtained in Example 1 of the present invention;

[0026] Figure 6 is the GF value of the product obtained in Example 1 of the present invention;

[0027] Figure 7 is the thermal conductivity of the product obtained in Example 1 of the present invention;

[0028] Figure 8 is the thermal conductivity of the product obtained by hot pressing;

[0029] Fig. 9 1 is a thermoelectric figure of merit of the product obtained in Example 1 of the present invention. DETAILED DESCRIPTION

[0030] In order to make the purpose, technical solution and advantages of the present invention more clearly understood, the present invention is further described in detail below in conjunction with the embodiments. It should be understood that the specific embodiments described herein are only used to explain the present invention and are not used to limit the present invention.

[0031] In order to enable those skilled in the art to fully understand how to implement the present invention in detail, this section is an explanatory embodiment that expands and describes the technical solution of the claims.

[0032] like Figure 1 As shown, the embodiment of the present invention provides a method for synthesizing Na by combining a self-propagating method and a cold pressing method. x The preparation method of CoO2 includes:

[0033] S101, dissolve sodium nitrate and cobalt nitrate hexahydrate in 100 ml of 72 g / L citric acid solution at a ratio of 1.1:2.

[0034] S102, heating the mixed solution on a hot plate at 300° C. until the solution becomes a viscous reddish-brown liquid, and continuing to heat, the viscous liquid will burn in a self-propagating manner, and finally a black precursor powder is obtained.

[0035] S103, the obtained black precursor powder is placed in a muffle furnace and calcined in an air atmosphere at 600-900°C for 1-2 hours to remove organic matter, and then a tablet press is used to apply a certain pressure to the obtained powder to obtain a disc-shaped Na x CoO2 polycrystalline block, the polycrystalline block is annealed again at 600-900℃ to improve its density.

[0036] The beaker in step S101 in the embodiment of the present invention is placed on a constant temperature heating magnetic stirrer and stirred at a speed of 500 r / min for 10 min.

[0037] The reaction process in step S102 in the embodiment of the present invention is completed in a fume hood.

[0038] The Na obtained in step S103 in the embodiment of the present invention x The pressure applied by CoO2 is 40MPa.

[0039] Example 1

[0040] (1) Dissolve 7.2 g of citric acid in 100 ml of deionized water, then add 1.768 g of NaNO3 and 11.005 g of Co(NO3)2·6H2O to the solution and stir thoroughly in a magnetic stirrer.

[0041] (2) After removing the magnet, the mixed solution is placed on a hot plate at 300°C and continues to be heated. The viscous liquid will burn in a self-propagating manner, and finally a black precursor powder is obtained.

[0042] (3) The obtained black precursor powder was placed in a muffle furnace and calcined for 2 h in an air atmosphere at 800 °C to remove organic matter. Then, a tablet press was used to apply a pressure of 40 MPa to the obtained powder to obtain a disc-shaped Na x CoO2 polycrystalline block, the polycrystalline block is annealed again at 800℃ to improve its density.

[0043] A method for synthesizing Na by combining a self-propagating method and a cold pressing method prepared in an embodiment of the present invention x CoO2 has high crystallinity and thermoelectric properties; and the single synthesis yield is large, easy to industrially produce, and has extremely high application value in waste heat recovery applications in high temperature areas. The resulting product morphology is as follows Figure 2The crystal structure characteristics of the obtained product are shown in Figure 3 The obtained nickel-doped Na x CoO2 thermoelectric materials have been successfully applied in the field of waste heat recovery. Its thermoelectric properties are as follows Figure 4-7 shown.

[0044] In order to prove the creativity and technical value of the technical solution of the present invention, this section provides application examples of the claimed technical solution on specific products or related technologies.

[0045] The present invention provides a method for synthesizing Na by combining a self-propagating method and a cold pressing method. x Na prepared by CoO2 powder preparation method x CoO2 thermoelectric materials can be used in the fields of industrial waste heat recovery, personalized refrigeration, biomedicine and flexible sensing. x CoO2 thermoelectric materials have been successfully applied in the field of temperature difference power generation. Figure 4-7 As shown, the embodiments of the present invention have achieved some positive effects during the development or use process, and do have great advantages compared with the prior art. The following content is described in combination with data, icons, etc. of the test process.

[0046] The Na prepared in Example 1 x CoO2 nano thermoelectric materials are used in the field of temperature difference power generation. The scanning electron microscope image is as follows: Figure 2 As shown, Na x CoO2 has a layered structure with small particles on the surface. These particles have a certain scattering effect on phonons and can reduce the thermal diffusion performance of the material. Figure 3 Shown is Na x The X-ray diffraction pattern of CoO2 nanothermoelectric material shows that the characteristic peak position indicates that Na x CoO2 nano-thermoelectric materials were successfully synthesized and have good crystallinity. Figure 4 Shown is Na x The Seebeck coefficient of CoO2 nanothermoelectric materials is in the range of 373K to 773K. x The Seebeck coefficient of CoO2 nanothermoelectric material increases monotonically with increasing temperature, reaching 89μV / K at 373K and 146μV / K at 773K. Figure 5 Shown is Na x The electrical conductivity of CoO2 nanothermoelectric materials is in the range of 373K to 773K. x The electrical conductivity of CoO2 nanothermoelectric material decreases monotonically with the increase of temperature, which is 7119S / m at 373K and 5000S / m at 773K. According to the above test data, we use PF = σ 2 S obtains the power factor of the material as Figure 6 As shown in Figure 2, the power factor of the material also increases monotonically with increasing temperature. On the other hand, the thermal conductivity of the material is as follows: Figure 7 As shown in Figure 1, the thermal conductivity decreases monotonically with increasing temperature in the range of 373K to 773K. The thermal conductivity is 0.9W / K·m at 373K and 0.8W / K·m at 773K. According to the calculation formula of thermoelectric figure of merit ZT=S 2 σT / κ, we get Na x The ZT value of CoO2 thermoelectric material is as follows Figure 7 As shown in the figure, it increases monotonically with increasing temperature in the range of 373K to 773K, and the ZT value reaches a maximum of 0.102 at 773K.

[0047] The preferred specific embodiments of the present invention are described in detail above. It should be understood that ordinary technicians in the field can make many modifications and changes based on the concept of the present invention without creative work. Therefore, all technical solutions that can be obtained by technicians in the technical field based on the concept of the present invention through logical analysis, reasoning or limited experiments on the basis of the prior art should be within the scope of protection determined by the claims.

Claims

1. A method for synthesizing Na by combining self-propagating method and cold pressing method x CoO 2 Preparation method of nano thermoelectric material, It is characterized in that The following steps are involved: Step 1, dissolving sodium nitrate and cobalt nitrate hexahydrate in a ratio of 1.1:2 in 100 ml of 72 g / L citric acid solution; Step 2, heating the mixed solution on a hot plate until the solution becomes a viscous reddish-brown liquid, and continuing to heat, the viscous liquid will burn in a self-propagating manner, and finally obtain a black precursor powder; Step 3: Place the obtained black precursor powder in a muffle furnace and calcine it in an air atmosphere at 600-900°C for 1-2 hours to remove organic matter. Then, a tablet press is used to apply a certain pressure to the obtained powder to obtain a disc-shaped Na x CoO 2 Polycrystalline block, polycrystalline block again at 600-900 ℃ cold pressing method to synthesize Na x CoO 2 To improve its density.

2. Na as claimed in claim 1 x CoO 2 Preparation method of nano thermoelectric material, It is characterized in that The beaker in step 1 was placed on a constant temperature heating magnetic stirrer and stirred at a speed of 500 r / min for 10 min.

3. Na as claimed in claim 1 x CoO 2 Preparation method of nano thermoelectric material, It is characterized in that The reaction process in step 1 was completed in a fume hood.

4. Na as claimed in claim 1 x CoO 2 Preparation method of nano thermoelectric material, It is characterized in that The heating treatment in step 2 is carried out in a fume hood, the wind speed needs to reach above 0.5m / s, and the heating treatment temperature is 300°C.

5. Na as claimed in claim 1 x CoO 2 Preparation method of nano thermoelectric material, It is characterized in that Na obtained in step 3 x CoO 2 The applied pressure was 40 MPa.

6. A method for synthesizing Na by combining self-propagating method and cold pressing method x CoO 2 Nano thermoelectric materials, It is characterized in that The Na x CoO 2 Nano thermoelectric material using the Na according to any one of claims 1 to 5 x CoO 2 The nano thermoelectric material is prepared by a preparation method.

7. A temperature difference power generation device suitable for high temperature areas, It is characterized in that The temperature difference power generation device utilizes the Na x CoO 2 Made of nano thermoelectric materials.

8. A temperature sensor, It is characterized in that The temperature sensor utilizes the Na x CoO 2 Made of nano thermoelectric materials.

9. A semiconductor refrigeration sheet, It is characterized in that The refrigeration device utilizes the Na x CoO 2 Made of nano thermoelectric materials.

Citation Information

Cited By

  • Co-doped ceramic-based thermoelectric material based on oxygen ion thermal diffusion and preparation method thereof

    CN119954513A